2022
DOI: 10.1097/bpb.0000000000000978
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes following adolescent athlete proximal hamstring apophyseal avulsion bone fragment excision and direct tendon-ischial tuberosity reattachment

Abstract: Apophyseal proximal hamstring bone avulsion is uncommon, occurring in adolescents following sudden forceful contraction of the musculotendinous unit. It can be severely disabling, preventing return to sport. This study assessed outcome following avulsed bone excision and direct hamstring tendon-ischial tuberosity reattachment using bone anchors. Validated hamstring-specific Sydney hamstring orthopaedic research evaluation PROMs were prospectively collected from consecutively treated athletes (7 elite and 11 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Of the 26 included articles, 7 studies 4 , 18 , 25 , 26 , 31 , 38 , 41 (n = 291 patients) reported on nonbracing postoperatively, and 19 studies ‖ (n = 985 patients) reported on some form of postoperative bracing. Five of the studies on bracing used hip bracing to limit excessive hip flexion postoperatively, 3 , 12 , 36 , 39 , 45 11 of the studies used a knee brace to limit excessive knee extension, 1 , 2 , 6 , 8 , 9 , 19 - 22 , 24 , 34 and 2 of the studies 29 , 37 used combined hip and knee bracing to limit both excessive knee extension and hip flexion.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 26 included articles, 7 studies 4 , 18 , 25 , 26 , 31 , 38 , 41 (n = 291 patients) reported on nonbracing postoperatively, and 19 studies ‖ (n = 985 patients) reported on some form of postoperative bracing. Five of the studies on bracing used hip bracing to limit excessive hip flexion postoperatively, 3 , 12 , 36 , 39 , 45 11 of the studies used a knee brace to limit excessive knee extension, 1 , 2 , 6 , 8 , 9 , 19 - 22 , 24 , 34 and 2 of the studies 29 , 37 used combined hip and knee bracing to limit both excessive knee extension and hip flexion.…”
Section: Resultsmentioning
confidence: 99%
“…The mean SANE score (93.6%) in the single braced study 8 that used the SANE tool was higher. In terms of general patient satisfaction, 96 of the 108 (88.9%) nonbraced patients in 4 studies 18 , 26 , 31 , 41 reported they were satisfied with their surgical outcome at the final follow-up. In the 12 braced studies ** that assessed patient satisfaction, 407 of 430 (94.7%) patients reported that they were satisfied with their surgical outcome.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations